1994
DOI: 10.1096/fasebj.8.2.8119495
|View full text |Cite
|
Sign up to set email alerts
|

Immunoelectron microscopic identification of cytoplasmic and nuclear G in S49 lymphoma cells

Abstract: The subcellular distribution of Gs alpha was characterized in S49 lymphoma cells with two polyclonal antisera directed against specific COOH- and NH2-terminal epitopes. Nonspecific binding was determined in each subcellular compartment by incubating cyc- S49 cells, known to be deficient in Gs alpha and its mRNA, with primary and secondary antisera. Small proportions of total specific binding sites were localized to the plasmalemma as well as the nuclear envelope. Because of their small size, these compartments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

1995
1995
2003
2003

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 0 publications
1
16
0
Order By: Relevance
“…Proliferating C 2 C 12 myoblasts exhibited a significant fraction of total cellular G s ␣ in cytoplasmic and nuclear compartments ( Fig. 1 A ), similar to our previous findings in S49 lymphoma cells (22). In striking contrast, intranuclear G s ␣ was not detected in C 2 C 12 myotubes (Fig.…”
Section: Immunolocalization Of G S ␣ Protein In Myoblasts and Myotubessupporting
confidence: 89%
See 3 more Smart Citations
“…Proliferating C 2 C 12 myoblasts exhibited a significant fraction of total cellular G s ␣ in cytoplasmic and nuclear compartments ( Fig. 1 A ), similar to our previous findings in S49 lymphoma cells (22). In striking contrast, intranuclear G s ␣ was not detected in C 2 C 12 myotubes (Fig.…”
Section: Immunolocalization Of G S ␣ Protein In Myoblasts and Myotubessupporting
confidence: 89%
“…We have previously shown that a substantial portion of total cellular G s ␣ is not associated with the plasmalemma but in-stead localizes to cytoplasmic and nuclear compartments of proliferating S49 lymphoma cells (22). In contrast, we have noted similar cytoplasmic but no specific nuclear G s ␣ immunoreactivity in postmitotic-differentiated cardiac myocytes (23).…”
Section: Introductionmentioning
confidence: 60%
See 2 more Smart Citations
“…Separate functions for the intracellular and cell surface receptors have been suggested using agents that putatively distinguish these receptors (8,9). Specifically, immediate effects have been proposed to be mediated by cell surface receptors, whereas regulation of expression of specific genes may be dependent upon intracellular receptors, consistent with the presence of signaling effectors in nuclei, including G proteins (14,15), ionic channels (16,17), phospholipases (12,18), adenylate cyclase (19), kinases (20), and NF-B (21). However, the specific identification of intracellular PAF receptors as well as their physiological functions, especially on organelles, which may explain their presumed involvement in gene regulation (8,22) in particular nuclei, has never been explicitly demonstrated.…”
Section: P Latelet-activating Factor (Paf)mentioning
confidence: 99%